Observations of Doppler and delay spreads on HF signals received over polar cap and trough paths at various stages of the solar cycle. Issue 5 (24th October 2013) - Stocker, A. J.; Warrington, E. M.; Siddle, D. R.
<x xml:space="preserve">Abstract</x> [1] Information on delay and Doppler spreading is of importance to designers and operators of digital communication systems within the HF band since modem performance rapidly deteriorates when delay and Doppler spreads exceed system dependent thresholds. The northerly ionosphere is a particularly challenging region in this regard as delay and Doppler spreads often significantly exceed those for similar length paths at midlatitudes. This paper presents results from an extensive set of measurements undertaken over three northerly paths: two subauroral paths aligned along the midlatitude trough (Uppsala to Bruntingthorpe and Nurmijärvi to Bruntingthorpe) and one path (Qaanaaq to Ny‐Ålesund) contained entirely within the polar cap. Measurements span the period from the 2009 solar minimum to July 2012, close to solar maximum and 2001, close to the previous solar maximum.